Lung cancer. Practice organization - Alberts, W Michael; Bepler, Gerold; Hazelton, Todd; Ruckdeschel, John C; Williams, Jr, James H (Chest, 2003)
The management of patients with suspected or known lung cancer is becoming increasingly complex. State-of-the-art care often requires input from many sources, including pulmonology, thoracic surgery, medical oncology, radiation oncology, pathology, and radiology. Valuable contributions to care also come from nursing, social work, psychology, psychiatry, pastoral care, and palliative care, among others. As a result, multidisciplinary input into care is vital. Patients with suspected lung cancer should be expeditiously evaluated and referred for management. Clear and understandable information on the diagnosis, treatment options, and possible outcomes should be provided. Treatment recommendations should be based on locally agreed-on adaptations of clinical practice guidelines. Provisions for ongoing care should be apparent to all concerned